2015
DOI: 10.1007/s13197-015-1907-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polysaccharide-based edible coatings enriched with dietary fiber on quality attributes of fresh-cut apples

Abstract: Little information is available regarding the incorporation of dietary fiber into edible films and coatings. In this work, apple fiber and inulin were incorporated into polysaccharide-based (alginate, pectine and gellan gum) edible coating formulations and their effects on the quality attributes of fresh-cut apples were evaluated. Antioxidant properties, color, firmness, sensory quality and microbial growth of fresh-cut apple were studied during 16 days of storage at 4°C. Results show that dietary fiber extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 23 publications
5
54
0
Order By: Relevance
“…These authors concluded that the addition of fibers could increase the nutritional value of this product. Also, Moreira et al . demonstrated that apple cubes coated with sodium alginate, pectin and gellan gum enriched with apple fiber (7 g kg −1 ) maintained their antioxidant capacity in a better way during the first week of refrigerated storage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These authors concluded that the addition of fibers could increase the nutritional value of this product. Also, Moreira et al . demonstrated that apple cubes coated with sodium alginate, pectin and gellan gum enriched with apple fiber (7 g kg −1 ) maintained their antioxidant capacity in a better way during the first week of refrigerated storage.…”
Section: Resultsmentioning
confidence: 99%
“…Apple fiber (AF) obtained from apple pomace and orange fiber (OF) were used at concentrations of 7 g kg −1 following the fiber:polysaccharide ratio suggested by Grigelmo‐Miguel and Martín‐Belloso . Inulin (IN) and oligofructose (OL) were used at 40 g kg −1 , selected according to Moreira et al . These authors selected the IN and OL concentrations based on a good solubility of fibers in the film‐forming solutions and following the requirements of The Code of Federal Regulations (Title 21, Part 101.54) for prebiotic effect of functional foods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreira et al introduced apple fiber and inulin into pectins solutions as edible coatings in fresh-cut "Golden delicious" apples evaluating the effect on the quality attributes [75]. Ascorbic acid was also added as antioxidant.…”
Section: Shelf-life Extension Of Fresh-cut Fruits and Vegetablesmentioning
confidence: 99%